Grade 10 life science teachers' understanding and development of critical thinking skills in selected schools in Namibia - Avia, Ndiyakuphi (Rhodes University, Faculty of Education, Department of Education, 2009)
The educational reform policy in Namibia adopted the principles and practice of learner-centred education, a policy based on constructivist epistemology. This approach emphasises that learners are constructors of knowledge and that they must discover information and construct their own learning. Constructivist techniques require the use of critical thinking through learners' active involvement in the learning process. The aim is for learners to use critical thinking to identify problems, ask questions, reason, examine and solve problems in real situations and make sound decisions. This approach provides learners with activities and experiences that stimulate them to learn to think for themselves and to ask questions. Therefore, teachers need to design activities that require learners to think critically and act independently through mastering these various modes of inquiry. The purpose of this study was to explore how the selected Grade 10 Life Science teachers understand and implement critical thinking in their teaching practice. I conducted the study in two secondary schools from the Omusati region in Namibia using a case study to gain insight into the implementation of critical thinking. Three data collection instruments: interviews, document analysis and class observations were used. The reason for conducting this study was to gain a better understanding of how teachers use various strategies to foster critical thinking skills in Life Science and the challenges they experience in teaching in secondary schools. The results of the study revealed that teachers have a theoretical understanding of what critical thinking implies and the role it plays in learning. They are also aware of the strategies used to develop critical thinking skills. However, these theoretical perspectives do not reflect in their teaching in that some of the strategies that the teachers used did not bring about meaningful learning. Learners are still required to recall factual knowledge, thus active involvement of the learners is limited. The study also revealed that there are specific issues that hamper the implementation of critical thinking, which include superficial understanding of learner-centered education, teacher-tell approach, overcrowded curriculum, inexplicit syllabus, lack of good examples from the textbooks and examinations, too short lesson periods, lack of language proficiency and lack of professional development. The findings indicate that despite the theoretical understanding of the teachers in this study, their actual practice of developing critical thinking skills is problematic. The study concludes that teachers should be encouraged to design better-structured activities in order to involve learners beyond just being listeners. In light of these findings, the study recognizes a need for ongoing in-service professional development to support teachers in modelling critical thinking to their learners and to teach them to think critically. The findings of the study will serve to inform both my and my colleague's professional practice as advisory teachers with regard to what to focus on when advising and supporting the teachers in schools.
Keywords: Education -- Namibia; Life sciences -- Study and teaching (Secondary) -- Namibia; Critical thinking -- Study and teaching (Secondary) -- Namibia; Education -- Curricula -- Namibia; Educational change -- Namibia; Teachers -- Training of -- Namibia